Systematic Literature Review on the Role of Islamic Leadership in Managing Social Funds to Reduce Socio-Economic Inequality - Reni Marlina, Chairani Firstia Rizal (Universitas Negeri Surabaya, 2025)
This study aims to analyze the role of Islamic leadership in managing social funds to reduce socio-economic inequality through a systematic literature review. Islamic social funds, such as zakat, infaq, sadaqah, and waqf, have significant potential to improve economic and social welfare, especially for the poor and marginalized groups. However, the effectiveness of their management largely depends on the quality of the leadership overseeing and managing these funds. Therefore, this research examines how various models of Islamic leadership, based on Sharia principles, can contribute to the management of social funds to reduce economic inequality in society. Based on the analysis of relevant studies, this research identifies several key factors in Islamic leadership, including transparency, accountability, and sustainability, that influence the success of social fund management. The results of this literature review indicate that leadership that is just and oriented towards the welfare of the community has a significant impact on wealth distribution and poverty reduction. This study also emphasizes the importance of a strategic approach in managing social funds to achieve more equitable social and economic justice.